2019
DOI: 10.14349/rlp.2019.v51.n3.7
|View full text |Cite
|
Sign up to set email alerts
|

Depression and satisfaction in different domains of life in dual-earner families: A dyadic analysis

Abstract: This study explored the spillover and crossover associations between depression and satisfaction with life, food-related life, and family life in dual-earner families. Questionnaires were administered to 303 dual-earner couples with adolescent children in Temuco, Chile. Both members of the couple answered the Depression Subscale of the Depression Anxiety and Stress scale-21, Satisfaction with Life scale, Satisfaction with Food-related Life scale, and the Satisfaction with Family Life scale. Using the actor-par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
1
13
0
3
Order By: Relevance
“…Unlike the previous variables, parents' mental health seems to have a key role associated with the family members' satisfaction with family life. The levels of depression, anxiety, and stress of both parents, and the levels of satisfaction with family life of each family member in the three profiles, support previous studies showing that an individual's mental health is negatively associated with their own satisfaction with family life (Lu et al, 2018), their partner's well-being (Marguerite et al, 2017), and satisfaction with family life (Schnettler et al, 2019), as well as their children's well-being (van Eldik et al, 2019). Notwithstanding, individuals with greater health problems might report greater social support because their health problems require more resources (Priest et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Unlike the previous variables, parents' mental health seems to have a key role associated with the family members' satisfaction with family life. The levels of depression, anxiety, and stress of both parents, and the levels of satisfaction with family life of each family member in the three profiles, support previous studies showing that an individual's mental health is negatively associated with their own satisfaction with family life (Lu et al, 2018), their partner's well-being (Marguerite et al, 2017), and satisfaction with family life (Schnettler et al, 2019), as well as their children's well-being (van Eldik et al, 2019). Notwithstanding, individuals with greater health problems might report greater social support because their health problems require more resources (Priest et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, mental health is focused on subclinical symptomatology of depression, anxiety, and stress (Lovibond & Lovibond, 1995). Studies have negatively associated mental health problems with individuals’ satisfaction in the family domain (Lu et al, 2018; Schnettler et al, 2019), and with their work–life balance (Haar et al, 2014). Research has also shown that individuals’ mental health can also affect their partners’ well‐being (Marguerite et al, 2017; Schnettler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent depression was also associated with impairment in family function ( Sireli and Aysev Soykan, 2016 ). On the other hand, people’s depression was negatively associated with their own level of satisfaction with life ( Bukhari and Saba, 2017 ; Schnettler et al., 2019 ). Furthermore, in a previous whole study of women living with breast cancer, depression was found to be an important mediator variable in the effect from social support to quality of life ( Kugbey et al., 2020 ) while a study also investigated the indirect effect of facebook addiction on life satisfaction through social anxiety and depression ( Foroughi et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sumado a lo anterior, dado que la depresión aumenta la irritabilidad, afecta el disfrute sexual y la comunicación, las parejas con un miembro deprimido presentan mayores dificultades y menor satisfacción con la relación reportada, tanto por hombres como por mujeres (Barry, Dubac & Barden, 2019;Kenny & Ledermann, 2010;Lamas, 2000). En cuanto al impacto en mujeres, estudios nacionales recientes en familias chilenas muestran que la depresión femenina se asocia negativamente con la satisfacción con la vida y la familia (Schnettler, et al, 2019),…”
unclassified